Young consumers’ intention towards future green purchasing in Malaysia - Sharaf, Muhammed Abdullah; Md Isa, Filzah; Al-Qasa, Khalid (Macrothink Institute, 2015)
Green marketing is all about marketing products that are considered environmentally safe.The purpose of this study is to examine the influence of price, time, and eco-label, on the intention of future green products purchasing among young Malaysian.In this study 250 questionnaires were distributed.The data was analyzed using reliability test, normality, correlation analysis, and multiple regressions.The results of this study showed that price, and time have a significant relationship with young consumers’ intention to purchase green products, however, eco-label had no influence on consumers’ intention to purchase green products.This research brings a better understanding on young consumers’ intention towards future green purchasing in Malaysia.